Design and Analysis of the 4‐Anilinoquin(az)oline Kinase Inhibition Profiles of GAK/SLK/STK10 Using Quantitative Structure‐Activity Relationships. (26th November 2019) - Asquith, Christopher R. M.; Laitinen, Tuomo; Bennett, James M.; Wells, Carrow I.; Elkins, Jonathan M.; Zuercher, William J.; Tizzard, Graham J.; Poso, Antti
Abstract: The 4‐anilinoquinoline and 4‐anilinoquinazoline ring systems have been the focus of significant efforts in prior kinase drug discovery programs, which have led to approved medicines. Broad kinome profiles of these compounds have now been assessed with the advent of advanced screening technologies. These ring systems, while originally designed for specific targets including epidermal growth factor receptor (EGFR), but actually display a number of potent collateral kinase targets, some of which have been associated with negative clinical outcomes. We have designed and synthesized a series of 4‐anilinoquin(az)olines in order to better understand the structure‐activity relationships of three main collateral kinase targets of quin(az)oline‐based kinase inhibitors: cyclin G associated kinase (GAK), STE20‐like serine/threonine‐protein kinase (SLK) and serine/threonine‐protein kinase 10 (STK10). This was achieved through a series of quantitative structure‐activity relationship (QSAR) analysis, water mapping of the kinase ATP binding sites and extensive small‐molecule X‐ray structural analysis. Abstract : Avoiding collateral damage : The 4‐anilinoquinoline and 4‐anilinoquinazoline scaffolds have been the focus of significant efforts in prior kinase drug discovery programs, which have led to a number of approved medicines. We have now designed and synthesized a series of 4‐anilinoquin(az)olines to better understand the structure‐activity relationships of three main collateral kinase targets of quin(az)oline‐based kinase inhibitors: cyclin G associated kinase (GAK), STE20‐like serine/threonine‐protein kinase (SLK), and serine/threonine‐protein kinase 10 (STK10). This was achieved through a series of quantitative structure‐activity relationship analysis and water mapping of the kinase ATP binding sites.